Traditional Risk Factors Are More Relevant than HIV-Specific Ones for Carotid Intima-Media Thickness (cIMT) in a Brazilian Cohort of HIV-Infected Patients - Pacheco, Antonio G. (PLoS One, 2015)
BACKGROUND: Combination antiretroviral therapy (cART) had a dramatic impact on the mortality profile in human immunodeficiency virus (HIV) infected individuals and increased their life-expectancy. Conditions associated with the aging process have been diagnosed more frequently among HIV-infected patients, particularly, cardiovascular diseases. METHODS: Patients followed in the Instituto de Pesquisa Clínica Evandro Chagas (IPEC) prospective cohort in Rio de Janeiro were submitted to the general procedures from the Brazilian Longitudinal Study of Adult Health, comprising several anthropometric, laboratory and imaging data. Carotid intima-media thickness (cIMT) was measured by ultrasonography, following the Mannheim protocol. Linear regression and proportional odds models were used to compare groups and covariables in respect to cIMT. The best model was chosen with the adaptive lasso procedure. RESULTS: A valid cIMT exam was available for 591 patients. Median cIMT was significantly larger for men than women (0.56mm vs. 0.53mm; p = 0.002; overall = 0.54mm). In univariable linear regression analysis, both traditional risk factors for cardiovascular diseases (CVD) and HIV-specific characteristics were significantly associated with cIMT values, but the best multivariable model chosen included only traditional characteristics. Hypertension presented the strongest association with higher cIMT terciles (OR = 2.51; 95%CI = 1.69–3.73), followed by current smoking (OR = 1,82; 95%CI = 1.19–2.79), family history of acute myocardial infarction or stroke (OR = 1.60; 95%CI = 1.10–2.32) and age (OR per year = 1.12; 95%CI = 1.10–1.14). CONCLUSIONS: Our results show that traditional cardiovascular disease (CVD) risk factors are the major players in determining increased cIMT among HIV infected patients in Brazil. This finding reinforces the need for thorough assessment of those risk factors in these patients to guarantee the incidence of CVD events remain under control.